MENINGKATKAN NILAI CBR TANAH SUB-GRADE DENGAN STABILISASI TANAH KAPUR - moch sholeh; yunaefi yunaefi (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
Poor soil properties and disadvantage when used as the basis of a building or road construction, including high plasticity, low shear strength, large volume or density changes and large shrinkage potential. Various methods are used to improve the strength of expansive clay soils, including by adding chemicals (chemical stabilization). Soil improvement that has been done is to mix the soil with lime, but only to review the dry density (γd). The purpose of this study is to explain the effect of adding lime to the soil on increasing CBR values, swelling, and knowing the optimum lime percentage in order to obtain maximum CBR and minimum swelling values. The results of the original soil swelling test showed a value of 9.14%, with the addition of lime percentage the swelling value showed a decrease. From the results of the addition of lime percentage showed the greatest decrease occurred in the addition of lime by 12% that is equal to 70.35%. So it can be concluded with the addition of lime will improve the original soil because it can reduce the value of swelling